Interaction between Chinese medicine and digoxin: Clinical and research update - Zhuang, Wei; He, Tao; Jia, Bei-Bei; Wang, Zhi-Zhou; Zhang, Lan; Dong, Xian-Zhe; Xi, Sheng-Yan (Frontiers in Pharmacology, 2023)
Digoxin is a widely used and long-standing cardiac drug. It has a narrow safety range, i.e., the amount leading to poisoning is only slightly higher than the amount necessary for treatment, and large individual differences in the effects of the drug have been observed. It is often used in combination with other drugs, but drug interactions have a great impact on the blood concentration of digoxin and lead to adverse reactions (ADRs), such as poisoning. Most of the reported drug interactions are with Western drugs, but interactions with traditional Chinese medicine (TCM) formulations have also been reported. However, there are many combinations of TCM formulations and Western drugs, and their efficacy is worth investigating. Therefore, it is important to understand the mutual effects between them. This paper summarizes and analyzes the TCM formulations that interact with digoxin and their mechanisms of action, in order to provide a reference for the rational and safe clinical use of digoxin.